1989
DOI: 10.1177/014107688908201009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Auditory Evoked Responses as a Measure of Recovery from Benzodiazepine Sedation

Abstract: The amplitude of the P300 component of auditory evoked responses was found to be depressed by benzodiazepine sedation and was subsequently used to monitor the recovery of volunteers sedated with midazolam. The amplitude of the evoked responses was found to be highly correlated with blood midazolam levels but to be no more sensitive than standard psychomotor testing in assessing recovery from sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…Summing up the current and earlier reported effects of benzodiazepines on event-related potentials (ERPs), midlatency ERPs (including P50) seem to be unaffected by benzodiazepines (Schwender et al, 1993), while the amplitudes of most if not all long-latency ERPs are decreased (Milligan et al, 1989;Nichols and Martin, 1993;Rockstroh et al, 1991;Semlitsch et al, 1995). Besides an enforced inhibition of neural circuits involved in the MMN generation by GABAergic interneurons, the observed reduction of the MMN could also stem from an attenuated efficacy in sensory information processing, as reflected by the decreased N100m (as a bottom-up process).…”
Section: Neuromagnetic Recordingsmentioning
confidence: 60%
See 1 more Smart Citation
“…Summing up the current and earlier reported effects of benzodiazepines on event-related potentials (ERPs), midlatency ERPs (including P50) seem to be unaffected by benzodiazepines (Schwender et al, 1993), while the amplitudes of most if not all long-latency ERPs are decreased (Milligan et al, 1989;Nichols and Martin, 1993;Rockstroh et al, 1991;Semlitsch et al, 1995). Besides an enforced inhibition of neural circuits involved in the MMN generation by GABAergic interneurons, the observed reduction of the MMN could also stem from an attenuated efficacy in sensory information processing, as reflected by the decreased N100m (as a bottom-up process).…”
Section: Neuromagnetic Recordingsmentioning
confidence: 60%
“…Similarly, no difference in MMN was revealed between schizophrenic patients treated with high vs those with low doses of anxiolytic and hypnotic drugs, including benzodiazepines . A reduction of the MMN by benzodiazepines seems to be, nevertheless, likely to some extent, since a diminution of event-related components caused by benzodiazepines was found in several studies, as for the N100 (Rockstroh et al, 1991;Semlitsch et al, 1995), P200 (Semlitsch et al, 1995), and P300 (Milligan et al, 1989;Nichols and Martin 1993;Rockstroh et al, 1991;Semlitsch et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Therapeutic doses of BDZs are reported to prolong the latency and decrease the amplitude of P300 in normal subjects (Berchou et al 1986;Milliggam et al 1989;Shinotoh et al 1989;Fujiwara et al 1991;Rockstroh et al 1991). The time courses of the effects of BDZ on P300 seem to correlate with its elimination half-life.…”
Section: Discussionmentioning
confidence: 99%
“…1991;Rockstroh et al 1991). However, these reports did not determine whether or not there is a relationship between cognitive impairments and other effects of BDZs such as sleepiness, even though it has been suggested that sedation affects the ERP (Berchou et al 1986;Milliggam et al 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation